2019
DOI: 10.1101/cshperspect.a036582
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent in the Genomics Era

Abstract: Medical informed consent assumes decision-making capacity, voluntariness, comprehension, and adequate information. The increasing use of genetic testing, particularly genomic sequencing, in clinical and research settings has presented many new challenges for clinicians and researchers when obtaining informed consent. Many of these challenges revolve around the need for patient comprehension of sufficient information. Genomic sequencing is complex-all of the possible results are too numerous to explain, and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 72 publications
0
13
0
1
Order By: Relevance
“…Defining informed consent for genomic testing has long been acknowledged as a challenging concept given the broad and uncertain nature of potential outcomes [36]. Evaluation of the MoC identified that most parents/guardians, recalled a discussion about genomic testing with a clinician, felt they had received enough information to make an informed decision about their child's test, and had no/minimal regret over their testing decision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining informed consent for genomic testing has long been acknowledged as a challenging concept given the broad and uncertain nature of potential outcomes [36]. Evaluation of the MoC identified that most parents/guardians, recalled a discussion about genomic testing with a clinician, felt they had received enough information to make an informed decision about their child's test, and had no/minimal regret over their testing decision.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, these finding highlights the challenges in discussing informed consent, particularly in paediatric mainstreaming setting where parents may be coping with stressors from their child's health condition. Future work on the MoC should consider options to improve the consent process, such as implementation of dynamic consent and patient-friendly videos and fact sheets [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…While participants better understood the community-informed IC, the perception that study participation results in improved care at the individual level highlights the challenge of navigating the threat of coercion and the need to engage in appropriate benefit sharing when conducting research in low-resource settings. Despite the additional explanations, the use of samples to conduct genetic studies and how genetic data are then shared was not well understood, suggesting the need for building research participants’ understanding of this concept through alternative strategies that have been successful in clarifying genetic studies and sharing genetic data, like video clips [40]. The clear preference for learning more about future users and uses, being told about incidental findings, and being able to access the results of future studies, means that cohort participants in Nicaragua and Colombia had the expectation that their shared data and samples could be linked to them so that they could be recontacted.…”
Section: Discussionmentioning
confidence: 99%
“…During the design process of HKGP consent protocol, consent protocols of other large-scale genomic projects such as the 100,000 Genomes Project, the latest consent policy and consent clauses for genomic research from the Global Alliance for Genomics and Health (GA4GH) were referenced, with the understanding that these frameworks have considered the opinions of the professionals and public [24][25][26][27] . To address the specific project details of HKGP, the Ethics Advisory Committee (EAC) [Figure 1] of HKGI advises on ethical issues in relation to the design and implementation, including the endorsement of the consent protocol of HKGP.…”
Section: The Thorough Process In Developing a Patient-focused Consent...mentioning
confidence: 99%